Religious-integrated therapy for religious obsessive-compulsive disorder in an adolescent: a case report and literature review - Md Rosli, Ahmad Nabil; Sharip, Shalisah; Wan Ismail, Wan Salwina (2018)
Religious obsessive-compulsive disorder (OCD) is relatively under-reported among adolescent and carries poorer outcome. We report a 20-year-old Muslim man who was diagnosed with religious OCD when he was 14 years old. He had recurrent blasphemous intrusive thoughts upon performing religious rituals which had hindered him from practising his religion. Despite being on tablet esticalopram 10 mg and conventional cognitive-behavioural therapy, the result was to no avail. A religious-integrated therapy was introduced by incorporating some of the Islamic values, knowledge, and practice during the exposure and response prevention therapy for five consecutive days along with cognitive restructuring. A considerable amount of symptom and functional relief was achieved. He excelled in his studies and equally important was able to resume practising his religion. Religious-integrated therapy is an untapped area that should be offered as the treatment option in certain cases where religion plays an important role in illness’s phenomenology and patient’s coping.
Keywords: Islam; Religious obsessive-compulsive disorder (OCD); Religiosity; religious-integrated therapy